Collagen microneedle patch loaded with copper-based antibacterial nanoparticles as well as preparation method and application of collagen microneedle patch

By doping copper-based antibacterial nanoparticles Cu-CpG@PDA into recombinant XVII collagen hydrogels and preparing collagen microneedle patches, the shortcomings of existing microneedle techniques in drug release control and material biocompatibility are solved, and the good photothermal conversion, antibacterial and skin regeneration capabilities of microneedle patches are achieved, and the treatment of bacterial infections and wound healing is achieved.

CN119770410AActive Publication Date: 2025-04-08CHANGZHOU UNIV

Patent Information

Application Number
CN202411693082.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-08
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing microneedle technology has limitations in the control of drug release rate and release time, and the materials used to construct microneedle patches have shortcomings in terms of biocompatibility, degradability and functionality, which affects the therapeutic effect.

Method used

Copper-based antibacterial nanoparticles Cu-CpG@PDA are doped into recombinant XVII collagen hydrogels and prepared collagen microneedle patches loaded with copper-based antibacterial nanoparticles through molds, and copper-based antibacterial nanoparticles are prepared using multi-stage assembly technology.

Benefits of technology

The microneedle patch has good photothermal conversion, antibacterial properties and skin regeneration capabilities, which can effectively treat bacterial infections and promote wound closure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770410A_ABST
    Figure CN119770410A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel microneedle preparation, in particular to a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and a preparation method and application of the collagen microneedle patch loaded with the copper-based antibacterial nanoparticles. The microneedle patch is prepared from the copper-based antibacterial nanoparticles, recombinant XVII type collagen and sodium alginate; wherein the copper-based antibacterial nano particles are Cu-CpG (at) PDA composite nano particles; the recombinant XVII type collagen protein is rCol XVII; the preparation method of the microneedle patch comprises the following steps: firstly, preparing Cu-CpG (at) PDA nanoparticles from antibacterial copper ions, a nucleic acid immunologic adjuvant CpG oligonucleotide and polydopamine (PDA); then, the Cu-CpG (at) PDA nano-particles are doped into recombinant XVII type collagen (rCol XVII) and sodium alginate, and collagen hydrogel loaded with the Cu-CpG (at) PDA nano-particles is prepared; finally, the hydrogel is laid in a mold, and the collagen microneedle patch loaded with the copper-based antibacterial nanoparticles is prepared after vacuum treatment, centrifugation and drying. The collagen microneedle patch disclosed by the invention has good photo-thermal conversion capacity, antibacterial property and skin regeneration capacity, and can be used for treating bacterial infection and promoting wound closure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hydrogel microneedle preparation, and in particular to a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, and a preparation method and application thereof. Background Art

[0002] Since the use of antibiotics began in the 1930s, the threat of bacterial infections has been greatly reduced. However, multidrug resistance (MDR) caused by the abuse of antibiotics is increasing. In this context, there is an urgent need to develop innovative non-antibiotic antibacterial methods. In recent years, with the advancement of nanotechnology, metal-based nanoantimicrobial agents such as gold, silver, copper (copper oxide), and zinc oxide have been widely used in the treatment of wounds infected with multidrug-resistant bacteria, and have achieved significant therapeutic effects. Among them, copper-based nanoparticles have excellent bactericidal ability, good biocompatibility and biosafety, and are widely used in dental antibacterial coatings and virus disinfection.

[0003] Although nano antimicrobial drugs have shown excellent antibacterial effects, their subcutaneous permeability is the first obstacle that needs to be solved. Microneedles (MNs), as a promising drug delivery platform, endow drugs with effective transdermal transport capabilities through minimally invasive skin damage. However, for situations where long-term or sustained drug release is required, the existing microneedle technology still has certain limitations in controlling drug release rate and release time. Currently, the types of materials used to construct microneedle patches are limited, and these materials still have certain limitations in biocompatibility, degradability and functionality. Some microneedle systems may not be able to achieve uniform and stable drug release, affecting the therapeutic effect. Summary of the invention

[0004] The embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and a preparation method and application thereof. The present application dopes copper-based antibacterial nanoparticles Cu-CpG@PDA into recombinant type XVII collagen hydrogel to obtain Cu-CpG@PDA loaded with Cu-CpG@PDA, and finally prepares a collagen microneedle patch loaded with copper-based antibacterial nanoparticles through a mold. The microneedle patch of the present application has good photothermal conversion ability, antibacterial performance and skin regeneration ability, and can be used to treat bacterial infections and promote wound closure.

[0005] To solve the above technical problems, in the first aspect, an embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, the microneedle patch being prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rCol XVII.

[0006] In some exemplary embodiments, the mass ratio of recombinant type XVII collagen and sodium alginate is 7:3; and the concentration range of Cu-CpG@PDA composite nanoparticles in the recombinant type XVII collagen and sodium alginate system is 0 mM to 20 mM.

[0007] In some exemplary embodiments, the microneedle patch includes a 30×30 array of circular needles; each circular needle has a base diameter of 300 μm and a height of 600 μm.

[0008] In some exemplary embodiments, the method for preparing copper-based antibacterial nanoparticles is as follows: first, Cu-CpG composite nanoparticles are prepared by co-assembly driven by coordination and electrostatic interactions between divalent copper ions and nucleic acid immune adjuvant CpG oligonucleotides; then, polydopamine PDA is coated on the surface of the Cu-CpG composite nanoparticles by in situ polymerization to prepare Cu-CpG@PDA composite nanoparticles.

[0009] In the second aspect, the present application also provides a method for preparing a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, comprising the following steps: step 1, dissolving recombinant type XVII collagen in a solvent to obtain a recombinant type XVII collagen solution, dispersing the copper-based antibacterial nanoparticles into the recombinant type XVII collagen solution, mixing and stirring for 2h to 6h to obtain dissolved collagen; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rColXVII; step 2, adding sodium alginate to the dissolved collagen, stirring evenly, and centrifuging to obtain a hydrogel; step 3, spreading the hydrogel into a mold, rolling it with a scraper, vacuuming or centrifuging so that the gel fully fills the needle tip, scraping off excess mother liquor with a scraper, and drying in a fume hood for 1h to 4h; step 4, adding a polyvinyl alcohol solution to the mold to form a microneedle base, drying naturally at room temperature, and obtaining a microneedle patch.

[0010] In some exemplary embodiments, in step 1, the solvent is a phosphate buffered saline solution with a pH of 7, the dispersion concentration of rCol XVII is 112 mg / mL to 224 mg / mL, and the dispersion concentration of Cu-CpG@PDA composite nanoparticles is 0 mM to 20 mM.

[0011] In some exemplary embodiments, in step 2, the dispersion concentration of sodium alginate is 24 mg / mL to 72 mg / mL.

[0012] In some exemplary embodiments, in step three, the hydrogel is centrifuged at a speed of 5000 rpm to 8000 rpm for 2 min to 5 min until all bubbles in the gel are exhausted.

[0013] In some exemplary embodiments, in step 4, the concentration percentage of the polyvinyl alcohol solution is 15% w / v to 20% w / v.

[0014] In addition, the embodiments of the present application also provide a use of a collagen microneedle patch loaded with copper-based antibacterial nanoparticles as described in the above embodiments in the preparation of a patch preparation for bacterially infected wounds.

[0015] The technical solution provided by the embodiments of the present application has at least the following advantages:

[0016] The embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and its preparation method and application. The microneedle patch is prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rCol XVII. The present application prepares copper-based antibacterial nanoparticles Cu-CpG@PDA by multi-stage assembly technology, and then dopes Cu-CpG@PDA into recombinant type XVII collagen hydrogel to obtain Cu-CpG@PDA loaded with Cu-CpG@PDA, and finally prepares a collagen microneedle patch loaded with copper-based antibacterial nanoparticles by a mold. Cu-CpG@PDA nanoparticles provide antibacterial properties, recombinant type XVII collagen can promote wound healing, and sodium alginate acts as a stabilizer and thickener to improve the stability of the sample and make it gel. The prepared antibacterial nanoparticle collagen microneedles have good biocompatibility, photothermal conversion effect, antibacterial properties and skin regeneration ability, and can be used for antibacterial treatment of bacterially infected wounds and skin healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplified descriptions do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.

[0018] Figure 1 Scanning electron microscopy images of blank MN and Cu-CpG@PDA rCol-MN prepared in Example 1 and Example 2.

[0019] Figure 2 This is an ultra-depth microscopy image of the Cu-CpG@PDA rCol-MN prepared in Example 2.

[0020] Figure 3A This is a transmission electron microscopy image of the copper-based composite nanoparticles prepared in Example 2.

[0021] Figure 3B This is the size distribution diagram of the copper-based composite nanoparticles prepared in Example 2.

[0022] Figure 4Schematic diagram of the mechanical properties of blank MN gel prepared in Example 3 and rCol XVII hydrogel loaded with Cu-CpG@PDA NPs.

[0023] Figure 5 Schematic diagram of the in vivo degradation performance of blank MN and Cu-CpG@PDA rCol-MN prepared in Example 4.

[0024] Figure 6 Schematic diagram of colony images and quantitative data of Staphylococcus aureus and Escherichia coli incubated with different samples prepared in Example 2 and Example 3 without or with near-infrared irradiation.

[0025] Figure 7 Schematic diagram of the cytotoxicity of different gels prepared in Example 6 to L929 cells.

[0026] Figure 8 The gelation conditions of samples prepared in different proportions in Example 7 are shown.

[0027] Fig. 9 The migration promotion effect of the copper-based composite nanoparticles prepared in Example 2 and the rCol XVII hydrogel loaded with Cu-CpG@PDA on L929 cells. DETAILED DESCRIPTION

[0028] As can be seen from the background art, in situations where long-term or sustained drug release is required, the existing microneedle technology still has certain limitations in controlling the drug release rate and release time.

[0029] Currently, the types of materials used to construct microneedle patches are limited, and these materials still have certain limitations in terms of biocompatibility, degradability and functionality. Some microneedle systems may not be able to achieve uniform and stable drug release, affecting the therapeutic effect. Collagen has been widely used in the field of biomaterials due to its excellent biological functions (promoting cell adhesion and proliferation), biocompatibility, low immunogenicity, rapid hemostasis, and biodegradation. In particular, type XVII collagen (Col XVII), as a transmembrane protein, constitutes semi-lipids, mediates the interaction between stem cells and surrounding cells and matrix, and regulates skin homeostasis, aging and wound repair. Compared with other types of collagen, Col XVII's multiple repeated collagen domains and non-collagen domains give it greater flexibility and diversity. It has special intermolecular interactions, such as intramolecular chain structures and intermolecular cross-linking, which enhances the stability and mechanical strength of the extracellular matrix. In addition, Col XVII has unique cell adhesion sites and signal transduction functions, which can regulate cell migration, proliferation and differentiation. Therefore, the present application uses recombinant type XVII collagen (rCol XVII) to construct a hydrogel microneedle patch for the loading of copper-based antibacterial nanoparticles and the treatment of skin infection wounds.

[0030] In order to solve the above technical problems, the embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and its preparation method and application. The microneedle patch is prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rCol XVII. The present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and its preparation method and application. The present application dopes the copper-based antibacterial nanoparticles Cu-CpG@PDA into the recombinant type XVII collagen hydrogel to obtain Cu-CpG@PDA loaded with Cu-CpG@PDA, and finally prepares the collagen microneedle patch loaded with copper-based antibacterial nanoparticles through a mold. The microneedle patch of the present application has good photothermal conversion ability, antibacterial performance and skin regeneration ability, and can be used to treat bacterial infections and promote wound closure.

[0031] The following will describe the various embodiments of the present application in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present application, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solution claimed in the present application can be implemented.

[0032] See also Figure 1The embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, which is prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rCol XVII.

[0033] The microneedle patch prepared in the present application is composed of Cu-CpG@PDA composite nanoparticles, recombinant type XVII collagen (rColXVII) and sodium alginate (SA). The present application uses divalent copper ions (Cu(Ⅱ)), nucleic acid immune adjuvant CpG oligonucleotides and dopa (DA) as raw materials, and prepares Cu-CpG@PDA antibacterial nanoparticles through DNA assembly and surface in situ polymerization technology; then, the Cu-CpG@PDA nanoparticles are doped into the hydrogel of recombinant type XVII collagen (rCol XVII) and sodium alginate (SA) to prepare the collagen hydrogel loaded with Cu-CpG@PDA nanoparticles; finally, the mixed hydrogel is spread into a polydimethylsiloxane (PDMS) mold, and after vacuum, centrifugation and drying, a collagen microneedle patch (Cu-CpG@PDA rCol-MN) loaded with copper-based antibacterial nanoparticles is obtained.

[0034] The copper-based antibacterial nanoparticle-loaded collagen microneedle patch prepared in the present application has an inner layer of Cu (II) that can break through the bacterial cell membrane, cause oxidative damage, and hinder bacterial metabolism, thereby bringing about an antibacterial effect; CpG can bind to Toll-like receptors (TLR9) to activate the innate immune response; polydopamine (PDA) has a structural stabilizing effect and photothermal conversion properties, and generates heat through near-infrared light irradiation to enhance the antibacterial effect; rCol XVII, as a transmembrane protein, can form semi-liposomes, mediate the interaction between stem cells and surrounding cells and matrix, and provide a role in regulating skin homeostasis, aging and wound repair; sodium alginate acts as a stabilizer and thickener.

[0035] In some embodiments, the mass ratio of recombinant type XVII collagen and sodium alginate is 7:3; the concentration range of Cu-CpG@PDA composite nanoparticles in the recombinant type XVII collagen and sodium alginate system is 0 mM to 20 mM.

[0036] In some embodiments, the microneedle patch includes a 30×30 array of circular needles; each circular needle has a base diameter of 300 μm and a height of 600 μm.

[0037] In some embodiments, the method for preparing copper-based antibacterial nanoparticles is: first, divalent copper ions and nucleic acid immune adjuvant CpG oligonucleotides are co-assembled to prepare Cu-CpG composite nanoparticles through coordination and electrostatic interaction-driven co-assembly; then, polydopamine PDA is coated on the surface of the Cu-CpG composite nanoparticles by in situ polymerization to prepare Cu-CpG@PDA composite nanoparticles.

[0038] In addition, the present application also provides a method for preparing a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, comprising the following steps:

[0039] Step 1, dissolving recombinant type XVII collagen in a solvent to prepare a recombinant type XVII collagen solution, dispersing copper-based antibacterial nanoparticles into the recombinant type XVII collagen solution, mixing and stirring for 2h to 6h to obtain dissolved collagen; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rCol XVII.

[0040] Step 2: Add sodium alginate to the dissolved collagen, stir evenly, and centrifuge to obtain a hydrogel.

[0041] Step 3: Spread the hydrogel into the mold, roll it with a spatula, vacuum or centrifuge to allow the gel to fully fill the needle tip, scrape off the excess mother liquid with a spatula, and dry it in a fume hood for 1h to 4h.

[0042] Step 4: Add polyvinyl alcohol (PVA) solution into the mold to form a microneedle (MN) substrate, and dry it naturally at room temperature to obtain a microneedle patch.

[0043] In some embodiments, in step 1, the solvent is a phosphate buffered saline (PBS) at pH=7, the dispersion concentration of rCol XVII is 112 mg / mL to 224 mg / mL, and the dispersion concentration of Cu-CpG@PDA composite nanoparticles is 0 mM to 20 mM.

[0044] In some embodiments, in step 2, the dispersion concentration of sodium alginate (SA) is 24 mg / mL to 72 mg / mL. Specifically, 24 mg to 72 mg of sodium alginate is weighed, added to the rCol XVII solution, stirred evenly, and then centrifuged.

[0045] In some embodiments, in step 3, the hydrogel is centrifuged at a speed of 5000 rpm to 8000 rpm for 2 min to 5 min until all bubbles in the gel are exhausted. The hydrogel is spread into a polydimethylsiloxane (PDMS) mold, and after vacuum, centrifugation, and drying, a collagen microneedle patch loaded with copper-based antibacterial nanoparticles (Cu-CpG@PDA rCol-MN) is obtained.

[0046] In some embodiments, in step 4, the concentration percentage of the polyvinyl alcohol solution is 15% w / v to 20% w / v.

[0047] In addition, the present application also provides an application of a collagen microneedle patch loaded with copper-based antibacterial nanoparticles as described in the above embodiment in the preparation of a patch preparation for bacterially infected wounds. The collagen microneedle patch (Cu-CpG@PDA rCol-MN) prepared in the present application is used to prepare a patch preparation for bacterially infected wounds. The Cu-CpG@PDA rCol-MN in the present application has good photothermal conversion ability, antibacterial properties and skin regeneration ability, and can be used to treat bacterial infections and promote wound closure.

[0048] Example 1 Preparation of Blank MN

[0049] Weigh 112 mg of recombinant type XVII collagen and dissolve it by ultrasonication with 1 mL of PBS at pH 7.0. Weigh 48 mg of sodium alginate (SA), add it to the dissolved collagen and stir evenly to obtain a hydrogel. Centrifuge (8000 rpm, 2 min) to remove the bubbles in the gel to form rCol XVII gel, and spread it into a mold (30*30 array, outer diameter of 30*30 mm, thickness of 8 mm). Roll it with a spatula, evacuate the needle tip so that the gel fully fills the needle tip, scrape off the excess mother liquor with a spatula, and dry it in a fume hood for 1 hour. Add 2 mL of 20% PVA solution to the mold and dry it naturally at room temperature to obtain a blank MN (Blank MN). Figure 1 shown.

[0050] Example 2 Preparation of Cu-CpG@PDArCol-MN

[0051] (1) 45 μL CuCl2 (200 mM), 40 μL CpG (200 μM) and 15 μL Tris buffer + Mg 2+ Solution (Tris buffer concentration is 20mM, Mg 2+ The mixture was mixed with 4% paraformaldehyde and 1% paraformaldehyde (with a concentration of 10 mM), heated at 95°C for 2 h to obtain Cu-CpG nanoparticles; the nanoparticles were dispersed in 0.2 mg / mL DA Tris buffer solution (10 mM, pH = 8.5), mixed, stirred for 3 h in the dark, centrifuged with water (12000 rpm, 15 min), washed 3 times, and freeze-dried to obtain Cu-CpG@PDA nanoparticles.

[0052] (2) Weigh 112 mg of recombinant type XVII collagen, add Cu-CpG@PDA nanoparticles, dissolve in 600 μL of PBS at pH 7.0, and stir in an ice bath for 4 h; weigh 48 mg of sodium alginate (SA), add it to the above solution, stir evenly, and centrifuge (8000 rpm, 2 min) to remove the bubbles in the gel to obtain rCol XVII hydrogel loaded with Cu-CpG@PDA NPs; spread it into a mold, roll it with a spatula, vacuum or centrifuge it so that the gel fully fills the needle tip, scrape off the excess mother liquor with a spatula, and dry it in a fume hood for 1 h; finally, add 2 mL of 20% PVA solution to the mold, dry it naturally at room temperature, and obtain a collagen microneedle patch loaded with Cu-CpG@PDA (Cu-CpG@PDA rCol-MN), as shown in FIG. Figure 2 The microneedle patch is composed of a 30×30 array of circular needles, each of which has a bottom diameter of 300 μm and a height of 600 μm. The ultra-depth microscopic image of Cu-CpG@PDArCol-MN prepared in Example 2 is shown in FIG. Figure 2 The transmission electron microscopy and size distribution of copper-based composite nanoparticles are shown in Figure 3A and Figure 3B shown.

[0053] Example 3 Collagen hydrogel gelation ratio test

[0054] Weigh different amounts of recombinant type XVII collagen and sodium alginate (total amount of 160 mg) to make the mass ratios 9:1, 8:2, 7:3, 6:4 and 5:5 respectively. First, add rCol XVII to 1mL of pH 7.0 PBS and ultrasonically dissolve it, then add the corresponding amount of sodium alginate and stir evenly, centrifuge (8000rpm, 2min) to remove bubbles, and observe the gelation. When the ratio of rCol XVII to sodium alginate is 9:1 or 8:2, gelation is not possible. Because it is necessary to ensure that the proportion of rCol XVII is as high as possible under the gelation conditions, a mass ratio of 7:3 is selected to prepare rCol XVII hydrogel. Figure 4 The mechanical properties of the blank MN gel and the Cu-CpG@PDANP-loaded rCol XVII hydrogel prepared in Example 3, where (a) is the rheological property and (b) is the change of viscosity with shear rate.

[0055] Example 4 Mechanical Properties of Microneedle Hydrogel Blank microneedle gel and Col XVII hydrogel loaded with Cu-CpG@PDA at a concentration of 8 mM were prepared, and the rheological properties of the hydrogel were evaluated on a rheometer. Different pressures (0, 150, 300, 450 g) were applied to the blank microneedle, and finally the changes in the microneedle tip were observed under the bright field of an inverted fluorescence microscope.

[0056] Example 5 Degradation Energy Test of Microneedle Hydrogel

[0057] Blank MN and Cu-CpG@PDArCol-MN were pressed on the back of ICR mice and fixed with wooden clamps for different time periods (0, 5, 10, 15, 20, and 30 min), and then the degradation degree of the microneedle tip was observed and photographed under bright field using an inverted fluorescence microscope. Figure 5 shown.

[0058] Example 6 Antibacterial coating test

[0059] Staphylococcus aureus (S. aureus) and Escherichia coli (E. coil) were cultured overnight in a shaker (37°C, 250 rpm) in tryptic soy broth (TSB and LB), and the bacteria in the logarithmic growth phase were obtained by centrifugation. The bacterial concentration was monitored by measuring the OD600nm value. When the OD600 value of the bacteria was diluted to 0.1, the concentration of Staphylococcus aureus was 2×10 8 CFU / mL. Then, take 50 μL of the concentration of 2×10 8 The bacterial suspension of S. aureus with CFU / mL was mixed with 50μL of different samples (2.5mMCu-CpG@PDA, rCol XVII hydrogel loaded with 2.5mM Cu-CpG@PDA) in a 1.5mL centrifuge tube, and sterile PBS was used as the control group (the phototherapy group was irradiated with 0.75W 808nm near-infrared light for 3min), and then placed in a 37℃ shaker at 250rpm for 1h. After the incubation, the mixed liquid of each sample group and bacteria was diluted 20,000 times, and 100μL was evenly applied to the corresponding bacterial culture medium plate. Three parallel samples were set for each group. After 16h of incubation in a biochemical incubator at 37℃, the colonies were counted.

[0060] Figure 6 Colony images and quantitative data of Staphylococcus aureus and Escherichia coli incubated with different samples prepared in Example 2 and Example 3 without or with near-infrared irradiation, wherein (a) is a colony image; (b) and (c) are quantitative data.

[0061] Example 7 Cytotoxicity Experiment

[0062] Take out the frozen mouse fibroblasts (L929) and put them in 37℃ sterile water and shake them back and forth to thaw. Then, draw 5mL of DMEM serum medium into a centrifuge tube, add the thawed cells, centrifuge (1000rpm, 5min) to remove the supernatant, resuspend the cell pellet at the bottom, and culture the cell suspension in a cell culture dish with 6-7mL DMEM serum medium. Passage until the cell viability is the best, and then perform cytotoxicity verification experiments. The counted cells were inoculated into a 96-well plate (1×10 4 / well), and then placed in a cell culture incubator (5% CO2) at 37°C for incubation for 12 hours. Use DMEM as the solvent to prepare 2.5mM Cu-CpG@PDA and Cu-CpG@PDAMN groups, and replace the well plate with 100μL sample per well, and DMEM culture medium alone is used as a control. After 24 hours of culture, the upper sample solution in the 96-well plate is aspirated, and 120μL DMEM / MTT solution (DMEM:MTT=1:6) is added. The 96-well plate is then placed in a cell culture incubator away from light for 4 hours. After staining, the upper MTT solution is removed, and 150μL DMSO solution is added to the 96-well plate. It is then shaken until the formazan is completely and evenly dissolved in DMSO, and the absorbance value at 490nm is measured with a microplate reader to determine the cell survival rate. The cytotoxicity of different gels prepared in Example 6 to L929 cells is as follows Figure 7 shown.

[0063] Example 8 L929 cell migration experiment

[0064] On the bottom of the six-well plate, three horizontal lines were drawn along the ruler with a marker pen as reference lines. Then, L929 cells were plated at 6 × 10 5 The cells were inoculated at a density of . After the cells were fully grown, two vertical lines were drawn in each well using a ruler and a pipette tip. These two lines intersected with the reference line to form a fixed observation point. The old culture medium was discarded and the wells were gently rinsed 2 to 3 times with PBS until the scraped cells were completely removed. Serum-free culture medium containing Cu-CpG@PDA nanoparticles or rColXVII hydrogel loaded with Cu-CpG@PDA was added, and the culture plate was placed in an incubator at 37°C and 5% CO2 for culture. At 0 hours, 12 hours, 24 hours and 48 hours, the cells were observed under a microscope at the same scratch position, and photographs were taken to monitor the changes in scratch width over time. The gelation of the samples prepared in different proportions in Example 7 is shown in Figure 2. Figure 8 The effect of the copper-based composite nanoparticles prepared in Example 2 and the rCol XVII hydrogel loaded with Cu-CpG@PDA on the migration of L929 cells is shown in FIG. Fig. 9 shown.

[0065] Based on the above technical scheme, the embodiment of the present application provides a collagen microneedle patch loaded with copper-based antibacterial nanoparticles and its preparation method and application. The microneedle patch is prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rColXVII. The present application prepares copper-based antibacterial nanoparticles Cu-CpG@PDA by multi-stage assembly technology, and then dopes Cu-CpG@PDA into recombinant type XVII collagen hydrogel to obtain Cu-CpG@PDA loaded with Cu-CpG@PDA, and finally prepares a collagen microneedle patch loaded with copper-based antibacterial nanoparticles by a mold. Cu-CpG@PDA nanoparticles provide antibacterial properties, recombinant type XVII collagen can promote wound healing, and sodium alginate acts as a stabilizer and thickener to improve the stability of the sample and make it gel. The prepared antibacterial nanoparticle collagen microneedles have good biocompatibility, photothermal conversion effect, antibacterial properties and skin regeneration ability, and can be used for antibacterial treatment of bacterially infected wounds and skin healing.

[0066] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. A collagen microneedle patch loaded with copper-based antibacterial nanoparticles, characterized in that: The microneedle patch is prepared from copper-based antibacterial nanoparticles, recombinant type XVII collagen and sodium alginate; wherein, The copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; The recombinant type XVII collagen is rCol XVII.

2. The collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 1, characterized in that: The mass ratio of recombinant type XVII collagen and sodium alginate is 7:3; The concentration range of Cu-CpG@PDA composite nanoparticles in the recombinant type XVII collagen and sodium alginate system is 0mM to 20mM.

3. The collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 1, characterized in that: The microneedle patch includes a 30×30 array of circular needles; the bottom surface of each circular needle has a diameter of 300 μm and a height of 600 μm.

4. The collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 1, characterized in that: The preparation method of the copper-based antibacterial nanoparticles is as follows: first, divalent copper ions and nucleic acid immune adjuvant CpG oligonucleotides are co-assembled to prepare Cu-CpG composite nanoparticles through coordination and electrostatic interaction-driven co-assembly; then, polydopamine PDA is coated on the surface of the Cu-CpG composite nanoparticles through in situ polymerization to prepare Cu-CpG@PDA composite nanoparticles.

5. A method for preparing a collagen microneedle patch loaded with copper-based antibacterial nanoparticles, characterized in that: The following steps are involved: Step 1, dissolving recombinant type XVII collagen in a solvent to obtain a recombinant type XVII collagen solution, dispersing copper-based antibacterial nanoparticles into the recombinant type XVII collagen solution, mixing and stirring for 2h to 6h to obtain dissolved collagen; wherein the copper-based antibacterial nanoparticles are Cu-CpG@PDA composite nanoparticles; and the recombinant type XVII collagen is rColXVII; Step 2: adding sodium alginate to the dissolved collagen, stirring evenly, and centrifuging to obtain a hydrogel; Step 3: Spread the hydrogel into the mold, roll it with a spatula, vacuum or centrifuge to make the gel fully fill the needle tip, scrape off the excess mother liquid with a spatula, and dry it in a fume hood for 1h to 4h; Step 4: Add polyvinyl alcohol solution into the mold to form a microneedle substrate, and dry it naturally at room temperature to obtain a microneedle patch.

6. The method for preparing the collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 5, characterized in that: In step 1, the solvent is a phosphate buffered saline solution with a pH of 7, the dispersion concentration of rCol XVII is 112 mg / mL to 224 mg / mL, and the dispersion concentration of Cu-CpG@PDA composite nanoparticles is 0 mM to 20 mM.

7. The method for preparing the collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 5, characterized in that: In step 2, the dispersion concentration of sodium alginate is 24 mg / mL to 72 mg / mL.

8. The method for preparing the collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 5, characterized in that: In step 3, the hydrogel is centrifuged at a speed of 5000 rpm to 8000 rpm for 2 min to 5 min until all bubbles in the gel are exhausted.

9. The method for preparing the collagen microneedle patch loaded with copper-based antibacterial nanoparticles according to claim 5, characterized in that: In step 4, the concentration percentage of the polyvinyl alcohol solution is 15% w / v to 20% w / v.

10. Use of the collagen microneedle patch loaded with copper-based antibacterial nanoparticles as claimed in claim 1 in preparing a patch preparation for bacterially infected wounds.

Citation Information

Patent Citations

  • Microneedle patch loaded with copper ion doped polydopamine as well as preparation method and application of microneedle patch

    CN112842989A

  • Bacteria responsive microneedle patch as well as preparation method and application thereof

    CN114432276A

  • Copper-based composite nano-particles with antibacterial and anti-tumor performance and preparation method of copper-based composite nano-particles

    CN117731635A

  • Recombinant XVII type collagen and expression system thereof

    CN117866077A

  • Extracellular vesicles loaded with structural biomolecules

    US20240301034A1

Cited By

  • Sterilization and anti-inflammation multi-layer microneedle patch with programmed response and preparation method of sterilization and anti-inflammation multi-layer microneedle patch

    CN121533969A

  • Galvanic cell effect hydrogen production anti-oxidation hydrogel microneedle patch and preparation and application thereof

    CN121971794A